2012
DOI: 10.1590/s0100-736x2012001200021
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and radiographic appearance of the capuchin monkey thoracic cavity (Cebus apella)

Abstract: Pesq. Vet. Bras. 32(12):1345-1350, dezembro 2012 1345 RESUMO.-[Aparência anatômica e radiográϐica da cavidade torácica do macaco-prego (Cebus apella).] O macaco-prego é muito comum tanto no norte, quanto no sul da The capuchin monkey is widespread both north and south of the Legal Amazon and in the Brazilian cerrado. Ten clinically healthy capuchin monkeys were submitted to an anatomical and radiographic study of their thoracic cavities. The radiographic evaluation allowed the description of biometric values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 22 publications
5
19
0
1
Order By: Relevance
“…25, 26 Recently, a positive correlation was described between the thoracic cavity length and the vertebral bodies, suggesting the use of these measurements to quantify increases in heart size in blackrumped agoutis and capuchin monkeys. 1,9 Similarly, the measurements of the length of the T4, T5, and T6 vertebras showed positive correlation with heart length and width, 1 sustaining the hypothesis of using the VHS to assess increases in heart volume in black-rumped agoutis, such as what was proposed by Buchanan and Bü cheler for dogs. 3,31 High correlation was also observed in the present study between the heart and thoracic diameter, endorsing the findings reported by the same authors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…25, 26 Recently, a positive correlation was described between the thoracic cavity length and the vertebral bodies, suggesting the use of these measurements to quantify increases in heart size in blackrumped agoutis and capuchin monkeys. 1,9 Similarly, the measurements of the length of the T4, T5, and T6 vertebras showed positive correlation with heart length and width, 1 sustaining the hypothesis of using the VHS to assess increases in heart volume in black-rumped agoutis, such as what was proposed by Buchanan and Bü cheler for dogs. 3,31 High correlation was also observed in the present study between the heart and thoracic diameter, endorsing the findings reported by the same authors.…”
Section: Discussionsupporting
confidence: 57%
“…1,4,11,24 Investigation of cardiac disease by diagnostic imaging modalities is widely used in veterinary medicine. 32 However, reference values have not yet been completely established for most of the wild species, and there is little information in the literature regarding standardization of techniques to investigate cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…In primates, variations in the number of thoracic vertebrae occur within a species . The number of thoracic vertebrae observed in this species (12–13) is similar to the common marmoset ( Callithrix jacchus ) .…”
Section: Discussionmentioning
confidence: 60%
“…The radiographic thoracic anatomy of the ring‐tailed lemur more closely resembles the common marmoset than other reported New and Old World monkeys . Variations exist in the normal radiographic thoracic anatomy of primates . Knowledge of the normal radiographic thoracic anatomy of individual species is important and fundamental for accurate diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Tal espécie já fora classificada como subespécie de S. apella (Groves et al 2005). Os S. apella são mais escuros, mais numerosos, apresentam maior distribuição geográfica entre os Sapajus, possuem diversas subespécies e extendem-se até outros países como Equador, Bolívia e Peru (Alves et al 2012, Eisenberg & Redford 1999, Groves et al 2005, Lynch Alfaro et al 2012a). …”
Section: Resultados E Discussão Características Fenotípicas E Biométrunclassified